Expected goals model with pre-shot movement, Part 3: 2018-2019 data - Novet, A. (2019)
In part 2 of this series the authors looked at the team and skater results from the 2016 - 2018 data that was used to train the xG model. That`s a pretty robust dataset, but it`s unfortunately a bit out of date. People care about this season, and past years are old news. So let`s take a look at the data that Corey Sznajder has tracked for 2018 - 2019 so far.